Associations with HIV testing in Uganda: an analysis of the Lot Quality Assurance Sampling database 2003–2012. Issue 4 (2nd April 2016) - Jeffery, Caroline; Beckworth, Colin; Hadden, Wilbur C.; Ouma, Joseph; Lwanga, Stephen K.; Valadez, Joseph J.
ABSTRACT: Beginning in 2003, Uganda used Lot Quality Assurance Sampling (LQAS) to assist district managers collect and use data to improve their human immunodeficiency virus (HIV)/AIDS program. Uganda's LQAS-database (2003–2012) covers up to 73 of 112 districts. Our multidistrict analysis of the LQAS data-set at 2003–2004 and 2012 examined gender variation among adults who ever tested for HIV over time, and attributes associated with testing. Conditional logistic regression matched men and women by community with seven model effect variables. HIV testing prevalence rose from 14% (men) and 12% (women) in 2003–2004 to 62% (men) and 80% (women) in 2012. In 2003–2004, knowing the benefits of testing (Odds Ratio [OR] = 6.09, 95% CI = 3.01–12.35), knowing where to get tested (OR = 2.83, 95% CI = 1.44–5.56), and secondary education (OR = 3.04, 95% CI = 1.19–7.77) were significantly associated with HIV testing. By 2012, knowing the benefits of testing (OR = 3.63, 95% CI = 2.25–5.83), where to get tested (OR = 5.15, 95% CI = 3.26–8.14), primary education (OR = 2.01, 95% CI = 1.39–2.91), being female (OR = 3.03, 95% CI = 2.53–3.62), and being married (OR = 1.81, 95% CI = 1.17–2.8) were significantly associated with HIV testing. HIV testing prevalence in Uganda has increased dramatically, more for women than men. Our results concurred with other authors that education, knowledge of HIV, and marriage (women only) are associated with testing for HIV and suggest that couples testing is more prevalent than other authors.